Quantifying lipid changes in various membrane compartments using lipid binding protein domains. (June 2017) - Várnai, Péter; Gulyás, Gergő; Tóth, Dániel J.; Sohn, Mira; Sengupta, Nivedita; Balla, Tamas
Graphical abstract: Highlights: Exact lipid distribution between various membranes is largely unknown. Many proteins contain lipid binding modules with some specificity. Some of these modules can be used to detect lipid distribution in live cells. Quantification of lipid changes using these tools is increasingly desirable. Abstract: One of the largest challenges in cell biology is to map the lipid composition of the membranes of various organelles and define the exact location of processes that control the synthesis and distribution of lipids between cellular compartments. The critical role of phosphoinositides, low-abundant lipids with rapid metabolism and exceptional regulatory importance in the control of almost all aspects of cellular functions created the need for tools to visualize their localizations and dynamics at the single cell level. However, there is also an increasing need for methods to determine the cellular distribution of other lipids regulatory or structural, such as diacylglycerol, phosphatidic acid, or other phospholipids and cholesterol. This review will summarize recent advances in this research field focusing on the means by which changes can be described in more quantitative terms.